2021
DOI: 10.1186/s12931-021-01624-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in precapillary pulmonary hypertension: a comparative analysis

Abstract: Background Risk stratification is essential to assess mortality risk and guide treatment in patients with precapillary pulmonary hypertension (PH). We herein compared the accuracy of different currently used PH risk stratification tools and evaluated the significance of particular risk parameters. Methods We conducted a retrospective longitudinal observational cohort study evaluating seven different risk assessment approaches according to the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…However, distinguishing high-risk patients who may require more intensive upfront therapies from the beginning is also an important issue. Recently, Sonnweber et al 17 underlined this issue and showed that 7 different risk assessment tools including noninvasive French model and REVEAL 2.0 lack accuracy to differentiate mortality between intermediate- and high-risk groups in a cohort consisted of idiopathic PAH, connective tissue-associated PAH, and chronic thromboembolic pulmonary hypertension. 17 Of note, according to our results, the prognostic separation between intermediate and high-risk groups remains challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, distinguishing high-risk patients who may require more intensive upfront therapies from the beginning is also an important issue. Recently, Sonnweber et al 17 underlined this issue and showed that 7 different risk assessment tools including noninvasive French model and REVEAL 2.0 lack accuracy to differentiate mortality between intermediate- and high-risk groups in a cohort consisted of idiopathic PAH, connective tissue-associated PAH, and chronic thromboembolic pulmonary hypertension. 17 Of note, according to our results, the prognostic separation between intermediate and high-risk groups remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sonnweber et al 17 underlined this issue and showed that 7 different risk assessment tools including noninvasive French model and REVEAL 2.0 lack accuracy to differentiate mortality between intermediate- and high-risk groups in a cohort consisted of idiopathic PAH, connective tissue-associated PAH, and chronic thromboembolic pulmonary hypertension. 17 Of note, according to our results, the prognostic separation between intermediate and high-risk groups remains challenging. It confirms a limitation of utilizing mainly noninvasive risk parameters to discriminate the prognostic risk between intermediate- and high-risk CHD-PAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zusammenfassend kann festgestellt werden, dass schon über die derzeitige Risikoeinteilung von PAH-Patienten eine Beurteilung der Prognose gut möglich ist [38]. Erste Daten zu überarbeiteten Prognose-Score-Modellen liegen vor und verbessern die Abschätzung der Prognose weiter [9,[39][40][41]. Die praktische Anwendung solcher Score-Systeme außerhalb von Studien wird durch die Verringerung der Anzahl von genutzten Variablen erleichtert.…”
Section: Schlussfolgerungunclassified
“…1,7-10 Sonnweber et al published a comparative analysis in which seven different risk assessment methods were compared, and concluded that there is still a need for new tools in intermediate-and high-risk precapillary PH patients, the present methods being inaccurate for predicting mortality. 11 In some clinical circumstances, modified, simplified score calculators that include little accessible data and undependable or invasive hemodynamic parameters can be used to predict 1-year mortality and long-term transplant-free survival in adult PAH or PAH associated with congenital heart disease (PAH-CHD) patients. [12][13][14][15] Over the few past decades, considerable interest in the role of iron status in idiopathic PAH and PAH-CHD has developed due to its potential impact on symptoms, exercise capacity (as assessed by the 6-minute walk distance [6MWD]), prognosis, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 7–10 Sonnweber et al published a comparative analysis in which seven different risk assessment methods were compared, and concluded that there is still a need for new tools in intermediate- and high-risk precapillary PH patients, the present methods being inaccurate for predicting mortality. 11 …”
Section: Introductionmentioning
confidence: 99%